Success rates, challenges and troubleshooting of left bundle branch area pacing as a cardiac resynchronization therapy for treating patients with heart failure - Zhang, Junmeng; Zhang, Yimin; Sun, Yaxun; Chen, Mengna; Wang, Zefeng; Ma, Changsheng (Frontiers in Cardiovascular Medicine, 2023)
Cardiac resynchronization therapy (CRT) is an accepted treatment of advanced heart failure patients with desynchronization. Left bundle branch area pacing (LBBaP) is a novel physiological pacing modality that appears to be an effective method for CRT. LBBaP has several advantages over the traditional biventricular-CRT (BIV-CRT), including a low and stable pacing capture threshold, a high success rate of implantation, a short learning curve, and high economic feasibility. However, the success rates of LBBaP is lower in the heart failure patients needing a CRT, because of myocardial fibrosis, nonspecific intraventricular conduction disturbance (IVCD), enlargement of the right atrium or right ventricle, etc. In this literature review, we summarize the success rates, challenges, and troubleshooting of LBBaP in heart failure patients needing a CRT.